2015
DOI: 10.1007/s13181-015-0485-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Plasma Exchange for Refractory Hemolysis After Brown Recluse Spider (Loxosceles reclusa) Envenomation

Abstract: Introduction The brown recluse spider (BRS) (Loxosceles reclusa) envenomation can lead to multiple complications, including hemolysis. We present a case of refractory hemolysis after a BRS bite treated with therapeutic plasma exchange (TPE). Case Report A 17-year-old female presented with fever, fatigue, and dyspnea. She was diagnosed with sepsis and received intravenous (IV) fluids, inotropic support, and antibiotics. On hospital day 1 she was noted to have skin lesion consistent with a BRS bite and developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Other studies have shown direct, immune-mediated mechanisms for thrombocytopenia and hemolysis in Loxosceles envenomation [ 4 , 10 , 13 ]. Additionally, numerous studies have found direct antiglobulin test-positive hemolysis 7 to 10 days into the course of Loxosceles envenomation, establishing an immune-mediated cause of hemolysis [ 4 , 10 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown direct, immune-mediated mechanisms for thrombocytopenia and hemolysis in Loxosceles envenomation [ 4 , 10 , 13 ]. Additionally, numerous studies have found direct antiglobulin test-positive hemolysis 7 to 10 days into the course of Loxosceles envenomation, establishing an immune-mediated cause of hemolysis [ 4 , 10 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loxosceles reclusa ( L. reclusa ), better known as the brown recluse spider, is a small hunting spider commonly found in the central and southeastern parts of the USA [ 1 ]. Loxoscelism denotes systemic effects from the L. reclusa venom.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis however is often missed or mislabeled as cellulitis or other skin infection [ 4 ]. The management of brown recluse spider bites is primarily supportive as there is no definitive intervention or guideline treatment [ 1 , 4 ]. Supportive care usually entails red blood cell transfusions, intravenous fluids, and local wound care [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of loxoscelism requiring TPE are rare in the literature. 10 In conclusion, because the early diagnosis of spider bites can facilitate multidisciplinary, live-saving approaches to treatment, loxoscelism should be considered in patients with skin necrosis, acute renal injury, and rhabdomyolysis.…”
mentioning
confidence: 99%